External public debt and balance of payments of CARICOM member states 1980-1996 (CCS GeorgetownGY, 1998)
Presents aggregates and indicators related to external public debt and balance of payments of 13 CARICOM member states. Data for Suriname was not available for inclusion in the report.
Additional copy located in the Office of the Secretary-General